A shariah overview of credit strengthening for equity-based Sukuk in the Islamic capital market in Malaysia / Dziauddin Sharif and Mohd Asyadi Redzuan - Sharif, Dziauddin; Redzuan, Mohd Asyadi (Academy of Contemporary Islamic Studies (ACIS), 2021)
The purpose of this paper to overview the potential of sukuk and shariah principles applied by industry players in the capital market in the process of strengthening credit mechanisms and practices based on previous studies. This study uses a qualitative approach in which fiqh books, journal articles and Islamic finance books and websites are the reference sources for data acquisition. Once collected, the information is selected, screened and classified into specific topics related to this study, which is to explore Islamic fiqh and finance experts’ view on the issue of credit consolidation in sukuk. Thus, this section divides the research methods into data collection and analysis. This study reviews the extent to which new sukuk-related studies have been able to grow, innovate and be able to resolve old issues that still haunt product structuring such as granting operator profit rights to sukuk investors. However, the survey also recognizes old findings that are still relevant such as the concept of tanazul which is the granting of profit rights to the management of sukuk if the profit rate exceeds expectations.